Conventional versus natural alternative treatments for leishmaniasis: A review - Passero, Luiz Felipe Domingues [UNESP]; Cruz, Lucas Antal [UNESP]; Santos-Gomes, Gabriela; Rodrigues, Eliana; Laurenti, Márcia Dalastra; Lago, João Henrique Ghilardi (Bentham Science Publishers, 2018)
Leishmaniasis is a neglected disease caused by protozoan belonging to the Leishmania genus. There are at least 16 pathogenic species for humans that are able to cause different clinical forms, such as cutaneous or visceral leishmaniasis. In spite of the different species and clinical forms, the treatment is performed with few drug options that, in most cases, are considered outdated. In addition, patients under classical treatment show serious side effects during drug administration, moreover parasites are able to become resistant to medicines. Thus, it is believed and well accepted that is urgent and necessary to develop new therapeutic options to overpass these concerns about conventional therapy of leishmaniasis. The present review will focus on the efficacy, side effects and action mechanism of classic drugs used in the treatment of leishmaniasis, as well as the importance of traditional knowledge for directing a rational search toward the discovery and characterization of new and effective molecules (in vivo assays) from plants to be used against leishmaniasis.
Keywords: Amphotericin; Conventional drugs; Ethnopharmacology; Leishmaniasis; Molecules; New drugs